The impact of Tolerance Limit on Cost of Quality - Omar, Mohamed K; Murugan, Sharmeeni; Abdullah, Rohana (2011)
In this paper, the recommended extensions by Chiadamrong [1] was successfully adopted and significant modifications was proposed when computing costs of quality model in a manufacturing system In the literature shows that there is strong connection exist between the tolerance designs with the quality characteristic of a product and the cost associate in achieving the specific quality of the product. With the intention of utilizing the reciprocal power model in determine the relation between the tolerance and the cost, the tolerance has to be converted and set to a standard value at different confidence level. The proposed costs of quality model was tested using real life data obtain from the industry and through simulation works, the results was generated.